Analysis and design of single phase voltage-frequency converter with optimized PI controller - M. Asna; H. Shareef; S.N. Khalid; A. Al Dosari; B. Hamad; M. Alhammadi; N. Aldarmaki (Institute of Advanced Engineering and Science, 2019)
This paper proposes a new voltage frequency converter (VFC) that converts both voltage and frequency to the required level of voltage and frequency in low voltage networks used in various countries. The proposed converter could be used as a universal power supply for sensitive AC loads. The converter is composed of, input voltage and frequency detection circuitry, full bridge boost rectifier and a DC to AC inverter. In addition, to improve the feasibility and performance of the converter, synchronous reference based PI (SRFPI) controller is adopted, where the system behaves similar to a DC-DC converter. The parameter selection of PI controller is done using a recent optimisation technique called Lightning Search Algorithm (LSA). The simulation of VFC is conducted in MATLAB/Simulink environment. The simulation results shows that LSA based PI controller provides better output voltage regulation with respect to the reference value under various load and input conditions.